Tax loss carryforwards: valuation of deferred tax assets - A. A. Aksent’ev (Вестник университета)
In the article, a comparative analysis of modern approaches to the assessment of deferred tax assets recognized for tax losses is carried out. The ambiguity of tax losses as an object of accounting observation is substantiated. Positive and negative effects of tax losses that do not allow to objectively qualify tax benefits as assets in accordance with conceptual criteria for their recognition are characterised. Prospective and retrospective factors for assessing the future recovery of deferred tax assets are presented. An example of accounting entries regarding recognition and recovery of tax losses using a valuation account is provided. The timing of prospective analysis is justified. Conservative and affirmative approaches to the assessment of tax losses in the financial accounting system are described. Based on the findings of the study, conclusions are given, and lines of future research are suggested.